The invasion of garlic mustard in North America and control measures - Zhang, Zhiyao (My University, 2022)
The purpose of this report is to investigate the impact of garlic mustard invasion on forest and control measures. Invasive species often cause harm to local ecosystems. Garlic mustard is an invasive herb native to Europe that was brought to North America in the early 1800s. Its seeds are small and numerous and spread easily. It is one of the most aggressive invasive species in Ontario. Garlic mustard invades undisturbed forests and its main effect is to reduce the abundance of soil and root mycorrhizal fungi, inhibiting the growth of native plants. Garlic mustard alters the diversity and activity of forest soil microorganisms. And studying the complex population dynamics of invasive species can help with planning and management. It is also important to choose appropriate control methods, mechanical control and chemical control (hand pulling, herbicide, etc.) on garlic mustard treatment effect is not obvious. The introduction of natural enemies in biological control is an efficient control method. Four weevil species have great potential in garlic mustard control. The possibility of eradicating invasive plants can be greatly improved by applying population genetics to biological control.
Keywords: Invasive species; Biodiversity; Ectomycorrhizal fungi; Ecological invasion; Biological control; Arbuscular mycorrhizal fungi